LOCALIZED TARGETING OF BIOMATERIALS FOLLOWING MYOCARDIAL INFARCTION; A FOUNDATION TO BUILD ON - Shuman, James A. (2013)
Acute coronary syndromes can give rise to myocardial injury-infarction (MI), which in turn promulgates a series of cellular and extracellular events that result in left ventricular (LV) dilation and dysfunction. Localized strategies focused upon interrupting this inexorable process include delivery of bioactive molecules and stem cell derivatives. These localized treatment strategies are often delivered in a biomaterial complex in order to facilitate elution of the bioactive molecules or stem cell engraftment. However, these biomaterials can impart significant and independent effects upon the MI remodeling process. In addition, significant changes in local cell and interstitial biology within the targeted MI region can occur following injection of certain biomaterials, which may hold important considerations when using these materials as matrices for adjuvant drug/cell therapies.